Analisis Dan Pengembangan Strategi Mitigasi Risiko Pada Proses Produksi Kayu Lapis (Plywood) (Studi Kasus: PT. SLJ Global Tbk) - Andi Deny; Anggriani Profita; Suwardi Gunawan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
PT. SLJ Global Tbk is wood industry factory located in Eas Kalimantan. The problem faced by the company is in the plywood production process. The purpose of this study was to determine the risks in the plywood production process at PT. SLJ Global Tbk, to determine the level of risk in the plywood production process using the FMEA method, and provide mitigation proposals to minimize risk in the plywood production process using the TOPSIS method. TheFMEA method, which is carried out by multiplying the severity, occurence, and detection ratings for each risk code and priority alternatives, is obtained using the TOPSIS method using Microsoft Excel. The critical risk results obtained are risks with code F6 which have an RPN value of 252, namely spare parts that are difficult to provide. The priority alternative results obtained for overcoming critical risks are optimizing maintenance performance (A2) with a rating of 1 which has a preference value (VI) of 1.0000.